2021
DOI: 10.1016/j.omto.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

m6A demethylase FTO induces NELL2 expression by inhibiting E2F1 m6A modification leading to metastasis of non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) represents one of the primary causes of cancer-related mortality all over the world. Following our initial finding of the upregulated expression of E2F transcription factor-1 (E2F1) in the NSCLC-related microarray, this study aimed to explore the regulatory role of E2F1 and underlying mechanism in NSCLC development. NSCLC cell viability, migration, and invasion were evaluated utilizing Cell Counting Kit 8 (CCK-8), 5-ethynyl-2′-deoxyuridine (EdU), wound-healing, and Transwell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…What's more, with population of studies in m6A, they were also found in prostate cancer 34 , renal cancer 35,36 , bladder carcinoma 37 , gastric cancer 38 , liver cancer 39 , and lung cancer 40 . However, what the role they played in SGCT in testicles were still unknown.…”
Section: Discussionmentioning
confidence: 92%
“…What's more, with population of studies in m6A, they were also found in prostate cancer 34 , renal cancer 35,36 , bladder carcinoma 37 , gastric cancer 38 , liver cancer 39 , and lung cancer 40 . However, what the role they played in SGCT in testicles were still unknown.…”
Section: Discussionmentioning
confidence: 92%
“… 18 Wang et al recently reported that E2F1, by activating the transcription of NELL2 gene, could enhance the migration, viability, and invasion of non-small cell lung cancer (NSCLC) cells as well as influence tumor progression and metastasis of NSCLC. 19 E2F2 could promote the lung cancer cell proliferation and invasion through Lnc-NNT-AS1/miR-3666/E2F2 axis. 20 Miao et al 21 reported that the expression of E2F2 could be regulated by transcription factor FLI1, the decrease of E2F2 resulted in arrest of lung cancer cell cycle and inhibition of lung cancer proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, FTO overexpression promotes cell growth, migration and metastasis, in an E2F1-dependent manner. Concomitantly, the level of m 6 A level in E2F1 mRNA is reduced upon FTO overexpression, suggesting that FTO’s function in lung cancer depends on its m 6 A demethylase activity 70 . Moreover, FTO mediated m 6 A demethylation is oncogenic in OSCC.…”
Section: ‘Context-dependent’ Function Of Fto In Cancermentioning
confidence: 99%